Characteristics of violence suffered by high school adolescents in a Brazilian state capital - Christine Baccarat de Godoy Martins; Lidiane Cristina da Silva Alencastro (Universidade Federal de Goias, 2015)
The aims of this cross-sectional study was to describe the characteristics of violence suffered by high school adolescent students of public schools in a Brazilian state capital. The data correspond to 456 adolescent victims of violence, collected by means of a questionnaire and processed by Epi-Info, in which analyses considered a value of p<0.05. Most of the adolescents were girls and the variables (gender, age, relationship with aggressor, frequency/length of time of abuse, place of occurrence and its interruption) varied according to the type of violence (bullying, physical, psychological, threat, sexual, witness, harassment, cyber-bullying, abandonment, neglect, child labor and parental alienation). The results represent the scene of violence suffered by adolescents, a reality that is poorly known and reported to official bodies, however, the descriptive data represent only part of the problem, highlighting the need to develop new studies to further investigate the various facets of the theme and to suggest new measures for facing violence in adolescence.